Geosynthetics in Antarctica: Performance of a composite barrier system to contain hydrocarbon-contaminated soil after three years in the field. Issue 5 (October 2016) - McWatters, R.S.; Rowe, R.K.; Wilkins, D.; Spedding, T.; Jones, D.; Wise, L.; Mets, J.; Terry, D.; Hince, G.; Gates, W.P.; Di Battista, V.; Shoaib, M.; et al.
Abstract: An overview of the design and performance of geosynthetics in composite barrier systems for biopiles used to remediate hydrocarbon-contaminated soil at Casey Station, Antarctica, is presented. Seven instrumented biopiles were constructed over three field seasons. To minimize the risk of hydrocarbon migration to groundwater, composite barrier systems were used (each using different combinations of geosynthetic clay liners (GCLs), high density polyethylene (HDPE) geomembranes (GMB), and geotextiles (GTXs)). One biopile used a co-extruded geomembrane (HDPE with an ethylene vinyl alcohol (EVOH) core). The liner system was subject to a combination of coupled phenomena that could interact and affect the GMB–GCL composite barrier performance. The exposure conditions involved potential freeze–thaw cycling, hydration–desiccation cycles, cation exchange, direct and diffusive exposure to hydrocarbons. The effect of these phenomena was investigated by monitoring GCL and GMB sacrificial coupons. GCL coupons were placed between the main GCL component and the main geomembrane component of the composite liner and GMB coupons placed between the main GMB sheet and the GTX protection layer. Coupons were exhumed from the biopiles each year. The exhumed GCL field moisture content values ranged from 162% to 22%. After three (3) years in the field, GCL coupons that had undergone at least one hydration/desiccation cycle showed no significant change in swell index values or fluid loss values. The measured hydraulic conductivity of exhumed GCL coupons from Biopiles 1 and 2 (3 × 10 −11 m s −1 ) was within the expected range and not significantly different from the values for virgin GCL. GMB coupons exhumed after three years from Biopiles 1 and 2 showed no significant change in oxidative induction time (OIT), melt flow index or tensile properties. Diffusion tests were performed as an index test for establishing the performance of the GMBs as a diffusive barrier to hydrocarbons, with permeation parameters for BTEX contaminants ranging from P g = 0.9–9.2 × 10 −13 m 2 s −1 for the exhumed GMB (with values depending on the contaminant and GMB). These values were similar to the parameters obtained for virgin GMBs and there was no significant change with field exposure, with GMBs appearing to be performing well.